(untitled) (Bangladesh Medical Journal Khulna, 2017)
Background: Acute pancreatitis is a potentially fatal disease. Mortality and morbidity depends on severity of the disease Objective: To find out the clinical presentation and to optimize the treatments. Method: This hospital based cross sectional descriptive study was performed to find out the clinical presentations of acute pancreatitis from the available clinical, biochemical, haematological and radiological data. Results: A total of 50 cases were studied. Age range was 13 to 74 yrs, with a peak incidence in the fourth decade. Male to female ratio were 1.78:1. Among the known aetiological factors 18% were due to gallstone disease and 10% due to alcoholism. Most common symptoms were upper abdominal pain (96%) and nausea, vomiting (88%). Among the clinical signs most common were abdominal tenderness (92%) and muscle guard (66%). In this study 82% patients had mild and 18% had severe acute pancreatitis. Overall mortality rate was 6%. Mortality was significantly higher (33.33%) in severe acute pancreatitis (33.3% vs 0%). Conclusion: A higher mortality was associated with concomitant medical or surgical diseases, but not to age or sex. A higher mortality was associated with leucocytosis but not to haemoglobin level. Among the biochemical parameters tested, a high blood glucose and serum creatinine level and a lower serum albumin and calcium level were significantly associated with a higher mortality. Bang Med J (Khulna) 2016; 49 : 7-12